PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. MANDALA MULTI FINANCE - Pransiska, Nike; Ekowati, Sri (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the effect of work discipline, work environment and work stress on employee performance at PT. Mandala Multi Finance Bengkulu city. This type of research is a type of quantitative descriptive research, the object of this research is the employees of PT. Mandala Multi Finance Bengkulu City, which is precisely located on Toba street, No. 24, Panorama,Singaran Pati district, Bengkulu City. The sampling technique, namely total sampling. The number of respondents in this study were 40 people. Methods of data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression Analysis Test, and Hypothesis Test, namely t test and f test. The results of this study can be concluded that the variable Work Discipline has a positive effect on Employee Performance, Work Environment has a positive effect on Employee Performance, Work Stress has a positive effect on Employee Performance, and Work Discipline, Work Environment and Stress together have a positive and significant effect on Performance Employees at PT. Mandala Multi Finance Bengkulu city. Keywords: Work Discipline, Work Environment, Work Stress, Employee Performance